Oxytocin modulates intrinsic neural activity in patients with chronic low back pain - Schneider, Isabella; Schmitgen, Mike; Boll, Sabrina; Roth, Corinna; Nees, Frauke; Herpertz, Sabine; Wolf, Robert Christian (European journal of pain, 2020)
Background Modulation of pain perception by oxytocin (OXT) has attracted increased scientific and clinical interest. Neural mechanisms underlying these effects are poorly understood. In this study, we aimed to investigate the effects of intranasally applied OXT on intrinsic neural activity in patients with chronic low back pain (cLBP). Methods Twenty-four male patients with cLBP and 23 healthy males were examined using resting-state functional magnetic resonance imaging. Participants were scanned twice and received either intranasally applied OXT (24 international units) or placebo 40 min before scanning. The fractional amplitude of low-frequency fluctuations (fALFF) was computed to investigate regionally specific effects of OXT on intrinsic neural activity. In addition a multivariate statistical data analysis strategy was employed to explore OXT-effects on functional network strength. Results Differential effects of OXT were observed in cLBP and healthy controls. FALFF decreased in left nucleus accumbens and right thalamus in cLBP and increased in right thalamus in healthy controls after OXT application compared to placebo. OXT also induced activity changes in bilateral thalamus, left caudate nucleus and right amygdala in cLBP. OXT was associated with increased medial frontal, parietal and occipital functional network strength, though this effect was not group-specific. Regression analyses revealed significant associations between left nucleus accumbens, left caudate nucleus and right amygdala with pain-specific psychometric scores in cLBP. Conclusions These data suggest OXT-related modulation of regional activity and neural network strength in patients with cLBP and healthy controls. In patients, distinct regions of the pain matrix may be responsive to modulation by OXT. Significance Our data suggest significant oxytocin-related modulation of intrinsic regional activity and neural network strength in patients with chronic low back pain and healthy controls. In patients, distinct regions of the pain matrix may be responsive to modulation by oxytocin. Therapeutic effects of oxytocin for improved pain treatment need to be further investigated.